Productivity, compatibility and economics of mustard (Brassica juncea) and lentil (Lens esculenta) intercropping system as influenced by moisture conservation practices and fertility levels under rainfed conditions - SINGH, T; RANA, K S; SATAPATHY, B S (The Indian Journal of Agricultural Sciences, 2014)
It can be summarized from the results obtained that mustard and lentil populations are well compatible in intercrop association with 2:2 paired row ratio, i.e. two row mustard paired (30/90 cm) followed by two rows of lentil as indicated by higher seed yield, mustard equivalent yield, HI, effective gain, LER, and SPI. Mustard crop appeared to be the dominant crop due to higher values of RCC, CR and aggressivity. Moisture conservation practices were not economically viable even though they positively affected seed and straw yield of mustard and lentil. The 100% RDF of mustard is recommended for mustard and lentil intercropping under rainfed conditions of northern India where these two crops are predominantly grown during the winter season.